2017
DOI: 10.1016/j.eurpsy.2017.01.1086
|View full text |Cite
|
Sign up to set email alerts
|

Depression in the Elderly with Chronic Medical Illness

Abstract: BackgroundThere is a bi-directional relationship between depression and chronic medical disorders.AimsThe objectives of our study were to measure the prevalence of depression in the elderly with chronic medical illness in primary care and to determine the socio-demographic and clinical factors related to depression.MethodsWe conducted a descriptive and analytical cross-sectional study of patients aged over 65, followed at the outpatient chronic diseases in Oudhref's district hospital (south of Tunisia) during … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Another study showed that QOL significantly affected the physical and mental components of sleep quality (35). Previous studies have also shown many factors contributing to poor sleep quality among seniors, including social and demographic factors (such as age, marital status, marriage, level of education) (36) and lifestyle factors (such as physical activity and anxiety and depression) (37), which all should also be considered.…”
Section: Discussionmentioning
confidence: 99%
“…Another study showed that QOL significantly affected the physical and mental components of sleep quality (35). Previous studies have also shown many factors contributing to poor sleep quality among seniors, including social and demographic factors (such as age, marital status, marriage, level of education) (36) and lifestyle factors (such as physical activity and anxiety and depression) (37), which all should also be considered.…”
Section: Discussionmentioning
confidence: 99%
“…LTCF make up a significant part of the social care and healthcare system in numerous societies, particularly in high-income countries, where they provide for the needs of older adults who are losing their autonomy [12]. These LTCF ensure that the most dependent older adults receive care following their loss of functional capacities, which might result in multiple falls, undernutrition, isolation and loneliness, and psychological suffering.…”
Section: Depression and Ltcfmentioning
confidence: 99%
“…The vast majority of care is aimed at residents’ somatic complaints, even though psychiatric disorders, particularly depression, are very widespread [13]. Moreover, because depression can negatively affect the treatment efficacy for numerous other medical disorders, even the most well-intentioned medical interventions can end up being less effective and more expensive [12].…”
Section: Depression and Ltcfmentioning
confidence: 99%